Spatial variation in species number, abundance and diversity of fish in Huatulco Bays, Oaxaca, Mexico. - Juárez-Hernández, Luis Gibran (2017)
Coral reef fish may adapt to their habitat characteristics, and the particular system intrinsic factors, may cause different fish compositions and structures. The present study aimed to determine the variation in number of species, abundance and diversity of fish communities in Huatulco bays of San Agustin, Riscalillo, Chachacual, Cacaluta, Maguey, Organo, Violín and La Entrega, from Oaxaca, Mexico. Fish communities were characterized between January 2009 and December 2010, with the use of visual census techniques. A total of 351 transects (10 x 2.5 m) were made, and for each one we analyzed the ichthyofauna species number, abundance and diversity. The analysis showed that for all variables, the highest values corresponded to Maguey, La Entrega, Órgano and Violín bays, while the lowest values corresponded to the San Agustín, Riscalillo, Chachacual and Cacaluta bays. The study identified significant differences in diversity (Kruskal-Wallis=18.71, P= 0.0091), and in the composition and structure of fish communities in the bays (ANOSIM= 0.278, P= 0.001). We observed a relationship between the number of fish species and number of coral species (Spearman=0.591, P< 0.05), while no relationship was found between the coral reef area and the number of fish species or their abundances. The number of coral species and the patchy arrangement of the coral cover created habitats that are structurally more complex, which affects the number of fish species. In areas with developed tourist infrastructure, recreational aquatic activities were found to affect the ichthyofauna behavior, abundance and diversity. The new information of this study may contribute to create and improve management, conservation and protection strategies for this important area as a whole interconnected complex.